Payment implants as an element of human enhancement technology - Sułkowski, Łukasz; Kaczorowska-Spychalska, Dominika (Human Technology, 2023)
Technology leads to changes that cause the biosphere and the techno-sphere to interpenetrate and co-evolve. This paper is part of a wider research project on the social acceptance of payment implants as an example of Human Enhancement Technology. At this stage, the focus was on identifying the characteristics attributed to users of this form of augmentation in order to assess social attitudes towards them. The study used the method of projection techniques, recognizing that real attitudes towards payment implants may be unconscious or reluctantly verbalized by a person. The research results indicate that the profile of people using payment implants as perceived by society and the set of characteristics attributed to them differs depending on whether the user is a woman or a man. Attention was also drawn to the differences in social and individual attitudes towards this form of augmentation.